Si Athenes était une île... - Pierart, Marcel (Studia Europaea Gnesnensia, 2011)
In the article, the author describes and comments on the policies of Athens after the crisis of 447–445 BC. The policy was naval in character, associated with the domination on the Aegean Sea. Thanks to the policy Athens became a power, albeit an unsteady one as the author proves, its weakness consisting in the fact that the polis was not an island.